Racial Disparity in Police Stop and Searches in England and Wales - Borooah, Vani K. (Journal of quantitative criminology, 2011)
Data published by the United Kingdom’s Ministry for Justice clearly shows that, compared to persons who were White, members of racial minorities in England, particularly Blacks, were far more likely to be stopped and searched by the police. The question is whether such racial disparity in stops and searches could be justified by racial disparities in offending? Or whether the disparity in stop and searches exceeded the disparity in offending? This paper proposes a method for measuring the amount of excess in racial disparity in police stop and searches. Using the most recently published Ministry of Justice data (for 2007/08) for Police Areas in England and Wales it concludes that while in several Areas there was no excess to racial disparity in police stop and searches, there was, on the basis of the methodology proposed in the paper, evidence of such excess in some Police Areas of England and Wales.